Pengembangan Usaha UMKM Kota Blitar melalui Pelatihan Digital Marketing dan Etika Bisnis - Engelien Yusniar Permanasari; Soebiantoro Soebiantoro (BADAN PENERBIT STIEPARI PRESS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening regional economic development, including in Blitar City. However, the rapid growth of digital technology has not been fully utilized by many MSME actors, particularly in the areas of marketing and ethical business management. This study aims to analyze the effectiveness of MSME development programs through digital marketing training and the strengthening of business ethics. A descriptive qualitative approach was employed, using interview, observation, and documentation techniques during the community service program implementation. The results show that digital marketing training successfully enhanced the capacity, creativity, and professionalism of culinary MSME actors in Blitar City. Participants were able to leverage digital media to expand market reach, increase sales, and manage customer relations more effectively. In addition, business ethics training improved participants’ understanding and moral awareness regarding honesty, responsibility, and integrity in business operations. The application of ethical values, both universal and Islamic-based principles, contributed to strengthening customer trust and supporting business sustainability. The synergy between digital competence and ethical awareness provided a positive impact on enhancing MSME competitiveness. Therefore, this program can serve as a model for technology- and morality-based local economic empowerment to strengthen community-based economic development.